Analisis Pelanggaran Hak-Hak Debitur dan Penyalahgunaan Wewenang Dalam Kasus Leasing Kendaraan Berdasarkan Hukum Positif di Indonesia - Lufthi, Al Daffa Naufal; Hutajulu, Dian Anggi Rahayu Kurnianingsih; Novel, Samirah; Lestari, Widya Tri; Ramadhani, Dwi Aryanti (Media Hukum Indonesia (MHI), 2024)
In a contractual agreement, problems often arise due to default or unlawful acts by one party that result in losses to the other party. As in the case that will be discussed in this article, the occurrence of unlawful acts caused by creditors that cause major losses. Leasing or known as Sewa Guna Usaha (SGU) is one method that is often used in Indonesia in the need for funding sources to obtain an asset such as in this case, namely a vehicle. This study aims to analyze case studies of violations of debtor rights in this installment agreement, and what form of responsibility the defendant is for his unlawful acts. The method used in this study uses a normative legal approach, namely analyzing and reviewing the legal issues being raised. In order to anticipate and protect legal interests, a contract must be prepared with clear clauses and is easy to understand. That way, if an action occurs that causes the agreement not to be completed or a loss, the party who is violated has the right to sue the violating party to court by fulfilling the elements of an unlawful act or default.